AUDIT SUMBERDAYA MANUSIA: STUDI KASUS PADA BALAI PENELITIAN BIOTEKNOLOGI PERKEBUNAN INDONESIA - Reswita, Reswita (Jurnal AGRISEP, 2009)
The aims of this study are to analyze human resources function in the employee’ perpectives In Center for Indonesian Plantation Biotechnology Research (Balai Penelitian Bioteknologi Perkebunan Indonesia), identify the aspects which should be improved, and identify functions needed to manage intensively.  Descriptive research method is used and non – parametric statistics including range criteria test, cartesius diagram, and Whitney and Kruskall Wallis are applied to analyze data gathered from 59 respondent who are censused.  The reserach concludes that human resource management has not been solidity.  For the future, its implementation should be improved for human resources development in this research center.